The Adult Changes in Thought (ACT) Medical Records Abstraction Project: A Resource for Research on Biological, Psychosocial and Behavioral Factors on the Aging Brain and Alzheimer’s Disease and Related Dementias - Nicole M. Gatto; Anne Renz; Sarah E. Tom; Mary Lyons; Jennifer A. Macuiba; Tammy S. Dodd; Bonnie K. Lind; Shelly L. Gray; Kelly Meyers; Eric B. Larson; Jennifer C. Nelson; Linda K. McEvoy; et al. (Brain Sciences)
Background: Adult Changes in Thought (ACT), a prospective cohort study, enrolls older adult members of Kaiser Permanente Washington. We describe an ambitious project to abstract medical records facilitating epidemiological investigation. Methods: Abstracted data include medications; laboratory results; women’s health; blood pressure; physical injuries; cardiovascular, neurological, psychiatric and other medical conditions. Results: Of 1419 of 5763 participants with completed abstractions, 1387 (97.7%) were deceased; 602 (42.4%) were diagnosed with Alzheimer’s Disease and Related Dementias; 985 (69.4%) had a brain autopsy. Each participant had an average of 34.3 (SD = 13.4) years of data abstracted. Over 64% had pharmacy data preceding 1977; 87.5% had laboratory data preceding 1988. Stroke, anxiety, depression and confusion during hospitalization were common among participants diagnosed with dementia. Conclusions: Medical records are transformed into data for analyses with outcomes derived from other ACT data. We provide detailed, unparalleled longitudinal clinical data to support a variety of epidemiological research on clinical-pathological correlations.